Advancing targeted therapies in pancreatic cancer: Leveraging molecular abberrations for therapeutic success - Gupta, Tanvi; Murtaza, Mohd (Progress in biophysics and molecular biology, 2025)
Pancreatic cancer is one of the most deadly with poor prognosis and overall survival rate due to the dense stroma in the tumors which often is challenging for the delivery of drug to penetrate deep inside the tumor bed and usually results in the progression of cancer. The conventional treatment such as chemotherapy, radiotherapy or surgery shows a minimal benefit in the survival due to the drug resistance, poor penetration, less radiosensitivity or recurrence of tumor. There is an urgent demand to develop molecular-level targeted therapies to achieve therapeutic efficacy in the pancreatic ductal adenocarcinoma (PDAC) patients. The precision oncology focuses on the unique attributes of the patient such as epigenome, proteome, genome, microbiome, lifestyle and diet habits which contributes to promote oncogenesis. The targeted therapy helps to target the mutated proteins responsible for controlling growth, division and metastasis of tumor in the cancer cells. It is very important to consider all the attributes of the patient to provide the suitable personalized treatment to avoid any severe side effects. In this review, we have laid emphasis on the precision medicine; the utmost priority is to improve the survival of cancer patients by targeting molecular mutations through transmembrane proteins, inhibitors, signaling pathways, immunotherapy, gene therapy or the use of nanocarriers for the delivery at the tumor site. It will become beneficial therapeutic window to be considered for the advanced stage pancreatic cancer patients to prolong their survival rate.